(untitled) (Jurnal Bahasa, 2020)
This study discusses the importance to Malay linguistics of phonological variation of Malay loan words as spoken by theindigenous Jakun people. The objective of this study is to describe,from the phonological point of view, the variety of Malay spoken by the Jakun people and to explain the importance of this variety of Malay to Malay linguistics. This study employs a qualitative descriptive method to describe the data collected from the field. The language data was collected by interviewing informants in five Jakun villages around Kluang in Johor. To describe the phonology of Jakun language, this study employs the rule ordering theory of Chomsky and Halle (1968). This study finds that the Jakun have borrowed many Malay words but with phonological differences. These phonological differences have given birth to a variety of the Malay language that differs slightly from standard Malay. Among the differences are the glottal stop insertion at the ends of words, the presence of the consonant [h] in vowel sequences, the presence of the consonant [h] at the beginning of words, the conversion of low vowels into high-mid vowels, the conversion of highmid vowels into high vowels, and the absence of vowel reduction. This variety of Malay demonstrates the dynamic nature of the Malay language in terms of its ability to be absorbed and adopted by other ethnic groups. Keywords: Indigenous people; Jakun; phonology of the Jakun language; Malay language variation; Malay linguistics